ANALYSIS COLLAGEN DENSITY ON DIABETIC AND NON-DIABETIC ACUTE WOUND MODEL: ANIMAL TRIAL USING WISTAR RATS - Maryunis, Maryunis; Bakri, Syakib; Patellongi, Ilhamjaya; Aman, Makbul; Tahir, Takdir; Rahayu, Ade Irma; Hasriyani, Hasriyani; Yusuf, Saldy (ETN Centre Indonesia, 2016)
Background: Neuropathy and peripheral vascular disease are two major factors that lead to diabetic wounds. Additionally, diabetic wound healing process takes a long time. Collagen is one indicator to assess wound healing. Aim: This study aimed to compare the wound healing process DM and non-DM In Wistar with acute wounds modeling that uses the density collagen as indicators. Methods: This study used a randomized design Post Test Control Group who uses Wistar as research objects. Wistar rats were divided into 2 groups: Wistar DM and Non-DM groups. The total sample were 30 individuals that consisted of 15 rats each group. Wistar DM was induced by injection of Streptozotocin (STZ) intraperitoneal single dose of 40-50 mg / kg. The wound were created by using punch biopsy of each group. The wound were followed up for 14 days. Data analysis was done using the Kolmogorov - Smirnov test with a confidence level of 95%. All data were analyzed by SPSS version 21.0 software (SPSS, Inc. Chicago, IL). Results: The density of collagen in DM group (20%) was lower than in non DM group (40%). However there were no significant difference in collagen density in both groups (p=0,375). Nevertheless, the percentage of collagen density is higher in non DM group compared with DM group (20.0%). This shows the tendency of the wound healing process in the group of Non - DM is better than DM group. This shows the tendency of the wound healing process in the group of Non - DM is better than DM group. Conclusion : There is a tendency that the wound healing in non ?DM group is better than in DM groups. More studies are needed in the future to confirm this findings. Key Words: Collagen Density, Acute Wound Model, DM